(untitled) (Global Journal of Medical Research, 2023)
Introduction Noise is an acoustic phenomenon producing an auditory sensation considered unpleasant or annoying Exposure to high sound levels over 85 dB A can affect the auditory system and other extra-auditory systems Our study had the general objective of evaluating the impact of noise related to noise exposure in the Lafarge Holcim Guinea factory Material and methods This was a prospective descriptive study lasting 6 months from March 01 2022 to September 01 2022 It focused on the 150 workers at the Lafarge Holcim Guinea plant and their work areas